Short Communication: New records of rare endemic Hose pygmy flying squirrel (Petaurillus hosei) in Sungai Rawog Conservation Area, Sabah, Malaysia - LAWRENCE ALAN BANSA; NUR AIN AWATIF MOHD-KANAPIAH; ARTHUR CHUNG; ZUL ASLAN JASLIN; NOOR HALIZA HASAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bansa LA, Mohd-Kanapiah NAA, Chung A, Jaslin ZA, Hasan NH. 2024. Short Communication: New records of rare endemic Hose pygmy flying squirrel (Petaurillus hosei) in Sungai Rawog Conservation Area, Sabah, Malaysia. Biodiversitas 25: 2937-2942. The Hose's pygmy flying squirrel, Petaurillus hosei (Thomas, 1900), is an International Union for Conservation of Nature (IUCN) data deficient species. Information on this species is lacking, and the sighting of this species is extremely rare in Borneo, particularly in Sabah. In Sabah, Malaysia, this species was documented only in Sepilok Forest Reserve more than 30 years ago. Furthermore, measurement records for this species are limited to only four specimens. A male P. hosei, was captured in the Rawog River Conservation Area, marking only the second record in Sabah and the fifth in Borneo. This individual was captured using a mist net attached to a pair of 8-meter-long telescopic poles, indicating that P. hosei primarily inhabits forests with medium to high canopy levels, as evidenced by their tree-dwelling habits. This individual's Head-to-Body (HB) dimensions are approximately 70.71 mm, with a tail length of 77.83 mm and hind legs measuring 19.46 mm. This species is morphologically similar to Petaurillus emiliae (Thomas, 1908), with single records from Baram, Sarawak, and Petaurillus kinlochii (Robinson & Kloss, 1911), only known from Selangor, Peninsular Malaysia. This discovery significantly contributes to the current photographic record and measurements of P. hosei from Sabah, Malaysia Borneo. Further research on the Sabah flying squirrel is crucial to enhance our understanding of the diversity, distribution, and behavior of this IUCN data deficient species. Therefore, comprehensive statewide survey involving mist netting and mid-level to canopy observations targeting old-growth forests is highly recommended.